French (Signifiances (Signifying), 2017)
The Chilean biologists Varela and Maturana have come up with the theory of languaging within the paradigm of enaction : human langage as an ethological component of the consensual domain of interactions participates in bringing forth a species-specific shared experienced world and shapes the co-evolution of the species and the environment. For their part, some linguists, some of them from the psychomecanics of langage theoretical background, are beginning to find an interest in this paradigm, and to apply it to some of their own objects of investigation, such as the role of the embodied lexical signifier in sense-making processes. This paper attempts to elicit the various entries into the « langage and enaction » field of study, to investigate into the divergences of the questionings, and to shed light on how those perspectives can work together.